Population Pharmacokinetics of an Indian F(ab')2 Snake Antivenom in Patients with Russell's Viper (Daboia russelii) Bites. - Geoffrey K Isbister; Kalana Maduwage; Ana Saiao; Nicholas A Buckley; Shaluka F Jayamanne; Shahmy Seyed; Fahim Mohamed; Umesh Chathuranga; Alexandre Mendes; Chandana Abeysinghe; Harindra Karunathilake; Indika Gawarammana; et al. (Public Library of Science (PLoS), 2015)
There is limited information on antivenom pharmacokinetics. This study aimed to investigate the pharmacokinetics of an Indian snake antivenom in humans with Russell's viper bites.Patient data and serial blood samples were collected from patients with Russell's viper (Daboia russelii) envenoming in Sri Lanka. All patients received Indian F(ab')2 snake antivenom manufactured by VINS Bioproducts Ltd. Antivenom concentrations were measured with sandwich enzyme immunoassays. Timed antivenom concentrations were analysed using MONOLIXvs4.2. One, two and three compartment models with zero order input and first order elimination kinetics were assessed. Models were parameterized with clearance (CL), intercompartmental clearance (Q), central compartment volume (V) and peripheral compartment volume (VP). Between-subject-variability (BSV) on relative bioavailability (F) was included to account for dose variations. Covariates effects (age, sex, weight, antivenom batch, pre-antivenom concentrations) were explored by visual inspection and in model building. There were 75 patients, median age 57 years (40-70 y) and 64 (85%) were male. 411 antivenom concentration data points were analysed. A two compartment model with zero order input, linear elimination kinetics and a combined error model best described the data. Inclusion of BSV on F and weight as a covariate on V improved the model. Inclusion of pre-antivenom concentrations or different batches on BSV of F did not. Final model parameter estimates were CL,0.078 L h(-1), V,2.2L, Q,0.178 L h(-1) and VP,8.33L. The median half-life of distribution was 4.6 h (10-90%iles:2.6-7.1 h) and half-life of elimination, 140 h (10th-90th percentilesx:95-223h).Indian F(ab')2 snake antivenom displayed biexponential disposition pharmacokinetics, with a rapid distribution half-life and more prolonged elimination half-life.